MOBILE APP INNOVATION IN MENTAL HEALTH MONITORING - Nooraisyah Nooraisyah; Sidderatul Akbar; Nunu Andriani (CV. Adiba Aisha Amira, 2024)
In the face of the global mental health challenge, technological innovation, mainly through mobile applications, offers wide potential to support mental health monitoring and interventions. With the increasing prevalence of mental health problems and limited access to conventional mental health services, mobile apps have emerged as important tools to provide easily accessible, timely, and personalised support. Research and development in this field has leveraged advances in artificial intelligence (AI), virtual reality (VR) and augmented reality (AR), wearable technologies, and predictive analysis to create innovative mental health solutions. This mobile application is designed not only for passive monitoring but also for active interventions that can improve the user's psychological well-being. This article examines various aspects of mobile application innovation in mental health, including chatbot-based therapy, immersive therapy with VR/AR, mental health monitoring with wearable technology, integration of health systems for coordinated support, and the importance of considering ethical as well as privacy aspects. By discussing recent and future potential mobile applications in mental health, the study aims to show how mobile technology can play a key role in addressing mental health challenges and improving the accessibility and effectiveness of mental health support.